Pengaruh Metode Latihan Up Hill dan Angkling (B Running) Menggunakan Beban Karet Resistance Pada Atlet Sprinter 100 Meter Siswa SMAN 2 Purbalingga (Universitas Negeri Semarang, 2022)
This research is in the form of experimental research. Researchers want to check whether there is an effect of pretest and posttest. Up hill running exercise is that the runner's feet are given a heavy enough load so that the runner tries to run as fast as possible on the uphill road. Efforts to run as fast as possible will increase leg muscle strength and leg power. The b running exercise in place using rubber also trains the strength of the small muscles in the thighs as well as the muscles that play a role in the legs, besides that it also creates coordination between the two athlete's feet so that the exercise is also effective for increasing sprint speed. The 100 meter sprint distance at SMAN 2 Purbalingga students reached an average of 4.77%, there was a significant effect on the variation of the B running technique using rubber on the 100 meter sprint distance to SMAN 2 Purbalingga students reaching an average of 4.41%, so the Up Hill method exercise was more effective. to increase the sprint distance of 100 meters for students of SMAN 2 Purbalingga